A Morphological Assessment of Cyclophorus perdix borneensis (Gastropoda:Cyclophoridae) at Sarawak - Nur Fatanah, Pini (Universiti Malaysia Sarawak (UNIMAS), 2022)
The focus of this project was on the land snail species of the Cyclophorus perdix borneensis that occupiesmostly limestone hills and other types of habitat in the western part of Sarawak. This study aimed to assessthe morphological variation of C. perdix borneensis populations from eight different localities at Sarawakbyusing their conchological measurement. The study sites for this project are Gua Raya, Bukit Parabinong, Bukit Pedak Bun, Fairy Caves, Gua Tupap, Kampung Benuk, Gunung Gading and UiTM. The measurement of the shell that have been taken to conduct the study was shell height (SH), shell width (SW), apertureheight (AH), aperture width (AW), umbilicus, shortest diameter (SD), parietal wall (PW) and columellar wall (CW). The results of Linear Discriminate Function Analysis (LDA) show that the shell fromGua Raya andBukit Parabinong are strongly separated from other localities. The correlation between shell height andshell width, and aperture height and aperture width of C. perdix borneensis show a positive correlation becauseboth the variables move in the same direction. We found that the largest shell of C. perdix borneensis wascollected around the limestone and secondary forest, while the smallest shell was originated fromthe primaryforest.